An integrated catch-at-age model for analyzing the variability in biomass of Pacific sardine (Sardinops sagax) from the Gulf of California, Mexico - Nevárez-Martínez, Manuel O.; Morales-Bojórquez, Enrique; Martínez-Zavala, María de los Ángeles; Villalobos, Héctor; Luquin-Covarrubias, Marlene A.; González-Máynez, Violeta E.; López-Martínez, Juana; Santos-Molina, J. Pablo; Ornelas-Vargas, Arelly; Delgado-Vences, Francisco (Frontiers in Marine Science, 2023)
Knowledge of the population dynamics and changes in the abundance of Pacific sardine fishery is relevant for fishery management. In this study, an integrated catch-at-age model (ASAP) was performed on 47 fishing seasons (1971‒2018) of Sardinops sagax in the Gulf of California, including five indices of relative abundance (survey catch rate, acoustic surveys, egg and larvae, spawning probability, and bird diet index). The ASAP model showed the importance of age group 0 (recruits); this is the most important age group in the Pacific sardine fishery, and its abundance has consequences for the variability of the total abundance of the species. In this study, the spawning and acoustic indices denoted the changes in abundance of Pacific sardine population better than the survey catch rate and bird diet ratio. Historically, the total biomass is estimated to have varied from 461 thousand to 4.82 million t. In the 1970s and 1980s, a peak biomass close to three million tons was reached, and in the second peak from the mid-1990s to the late 2000s, the total biomass varied between 3.26 and 4.82 million t. When the spawning biomass was at least 750 x 103 t, the recruitment (age group 0) showed high values, promoting high catches in the subsequent years. The annual fishing mortality estimates did not show a rise related to the periods of high harvestable biomass; therefore, the catch records were low in comparison to the harvestable biomass estimated from ASAP, and the annual fishing mortalities were less than 0.22 during periods of high abundance. The changes in biomass and the variability observed in the Pacific sardine fishery were validated for the model diagnostics; the retrospective patterns did not identify poor fits to data, therefore the robustness of the model can be used for management purposes. According to the Kobe phase plot, the Pacific sardine fishery in the Gulf of California has been fully exploited with an apparent stable level of harvest.